BSE in Northern Ireland: epidemiological patterns past, present and future - Ferguson,NM; Ghani,AC; Donnelly,CA; Denny,GO; Anderson,RM (Proc Biol Sci, 1998)
By 30 January 1998, there had been 170,259 confirmed cases of BSE in Great Britain (GB), 1766 confirmed cases in Northern Ireland (NI) (2 January 1998), and 276 confirmed cases in the Republic of Ireland (31 January 1998). Analysis of the epidemiological patterns in the NI epidemic reveals significant clustering of cases in herds and counties. The observed clustering of cases within herds results in lower per capita incidence of BSE in previously unaffected herds, providing support for the introduction of a certified herd scheme in NI. By fitting a backcalculation model to the case data, we can estimate the number of animals infected with the aetiological agent of BSE and project the number of future cases. We predict that the epidemic will decline rapidly, with approximately 99 cases (95% confidence interval 30,504) occurring in the five year period 1997-2001.